Impact of a Centralized Inpatient Hospice Unit in an Academic Medical Center. (September 2016) - Jegier, Briana J.; O'Mahony, Sean; Johnson, Julie; Flaska, Rita; Perry, Anthony; Runge, Mary; Sommerfeld, Teri
Objective: Rush University Medical Center (RUMC) and Horizon Hospice opened the first centralized inpatient hospice unit (CIPU) in a Chicago academic medical center in 2012. This study examined if there was a difference in cost or length of stay (LOS) in a CIPU compared to hospice care in scattered beds throughout RUMC. Study Design and Methods: This retrospective, cross-sectional study compared cost and LOS for patients admitted to the CIPU (n = 141) and those admitted to hospice scattered beds (SBM) throughout RUMC (n = 56). Results: The CIPU patients had a median LOS of 6.0 days versus 2.0 days for SBM patients. Conclusions: The CIPU patients had longer hospice LOS but lower hospital costs. Academic medical centers may benefit from aggregating hospice beds.